Faktor-faktor yang berhubungan dengan obesitas pada anak sekolah menengah atas - Saraswati, Ika; Rilyani, Rilyani; Aprina, Aprina (THE JOURNAL OF Mother and Child Health Concerns, 2024)
Background: Obesity is a problem that attacks all ages, including children and adolescents. According to WHO in 2017, more than 340 million children and adolescents aged 5-19 years were obese in 2016. The prevalence of obesity in children and adolescents aged 5-19 years increased sharply from only 4% in 1975 to more than 18%. in 2016. Purpose: To find out the factors associated with obesity in teenagers at Darul Fattah High School Bandar Lampung in 2021. Method: This type of quantitative research uses a cross sectional design and the research population is high school students aged 15-18 years at Darul Fattah High School Bandar Lampung with a total of 67 respondents using simple random sampling techniques. The instrument in this research used a questionnaire sheet and bivariate analysis used the Chi-Square test. Results: The Chi-Square obesity statistical test obtained p-value = 0.030 so that p-value < α (0.000 < 0.05) so H0 was rejected with an Odd Ratio value of 0.779. Conclusion: There are factors related to the incidence of obesity in children at Darul Fattah High School Bandar Lampung in 2021. Suggestion: For Darul Fattah High School Bandar Lampung to further improve outreach programs to the community, especially for children who are at risk of obesity.   Keywords: Children; Obesity; Problems.   Pendahuluan: Obesitas merupakan masalah yang menyerang segala usia, termasuk anak-anak dan remaja. Menurut WHO pada tahun 2017, lebih dari 340 juta anak dan remaja usia 5-19 tahun mengalami obesitas pada tahun 2016. Prevalensi obesitas pada anak dan remaja usia 5-19 tahun meningkat tajam dari hanya 4% pada tahun 1975 menjadi lebih dari 18%. pada tahun 2016. Tujuan: Untuk mengetahui faktor-faktor yang berhubungan dengan obesitas pada anak usia remaja di SMA Darul Fattah Bandar Lampung tahun 2021. Metode: Jenis penelitian kuantitatif menggunakan desain cross sectional dan populasi penelitian ini adalah anak SMA usia 15-18 tahun di SMA Darul Fattah Bandar Lampung dengan jumlah 67 responden dengan menggunakan teknik simple random sampling. Instrumen dalam penelitian ini menggunakan lembar angket dan analisis bivariat menggunakan uji Chi-Square. Hasil: Uji statistik obesitas Chi-Square diperoleh p-value = 0.030 sehingga p-value < α (0.000 < 0.05) maka H0 ditolak dengan nilai Odd Ratio 0.779. Simpulan: Terdapat faktor-faktor yang berhubungan dengan kejadian obesitas pada anak di SMA Darul Fattah Bandar Lampung Tahun 2021. Saran: Bagi SMA Darul Fattah Bandar Lampung agar lebih meningkatkan program penyuluhan kepada masyarakat khususnya bagi anak-anak yang berisiko mengalami obesitas.